An Invitation to Critical Mathematics Education - Skovsmose, Ole.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
An Invitation to Critical Mathematics Education deals with a range of crucial topics. Among these are students$1 (Bforeground, landscapes of investigation, and mathematics in action. The book is intended for a broad audience: educators, students, teachers, policy makers, anybody interested in the further development of mathematics education. The book discusses concerns and preoccupation. This way it provides an invitation into critical mathematics education.s
Keywords: Education; Mathematics; Education; Mathematics Education